2021
DOI: 10.52711/0974-360x.2021.00379
|View full text |Cite
|
Sign up to set email alerts
|

A Bioanalytical Method for Quantification of Telmisartan in rat Plasma; Development, Validation and Application to Pharmacokinetic Study

Abstract: The telmisartan was determined in a rat plasma using developed and validated a reversed-phase high performance liquid chromatographic (HPLC). The pre-treatment of the plasma sample involving liquid-liquid extraction using ethanol as the extracting solvent. The HPLC method validation has been shown a linear calibration curve over a plasma concentrations range of 0.7 to 10µg/mL with a correlation coefficient of 0.9979, the limit of detection and the limit of quantification were determined to be 0.025µg/ml and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As previously mentioned, some of the bioanalytical studies have been performed to determine the pharmacokinetic parameters of TEL from animal plasma using different analytical instruments, such as UPLC–MS and LC–MS/MS (Al‐Japairai et al, 2021; Anusha et al, 2017; Chen et al, 2016; Sengupta et al, 2017). From the reported literature, we observed that previous studies have focused on TEL alone or in combination with other drugs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, some of the bioanalytical studies have been performed to determine the pharmacokinetic parameters of TEL from animal plasma using different analytical instruments, such as UPLC–MS and LC–MS/MS (Al‐Japairai et al, 2021; Anusha et al, 2017; Chen et al, 2016; Sengupta et al, 2017). From the reported literature, we observed that previous studies have focused on TEL alone or in combination with other drugs.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive literature review revealed several chromatographic techniques for analyzing the combination in pharmaceutical formulations for TEL (Al‐Japairai et al, 2021; Sengupta et al, 2017). However, there is no documented formulation for GA as a specific active pharmaceutical component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the LOD and LOQ were measured by injecting the lowest detectable concentration in the linearity curve 6 times, and the standard deviation was calculated. Based on that standard deviation and curve slope, the LOD and LOQ of the analyte were mathematically estimated using the following equations [ 38 ]. To check precision, one concentration level (10 µg/mL) of paracetamol was spiked in the sample solution and injected six times; the concentration level is hereby termed as spiking solution.…”
Section: Methodsmentioning
confidence: 99%
“…Veeran et al [5] have mentioned its molecular mass was found to be 296.403 g/mol. AL-Japairai et al [6] mentioned that it is one of the synthetic estrogens that decreases luteinizing hormone to decrease endometrial vascularization and Bao et al [7] have identified that some of the drugs activity mainly depends on design parameters and also on in vitro release from intrauterine systems and also some of the drugs such as ethinylestradiol acts by decreasing gonadotrophic hormone to prevent ovulation. The chemical structure of ethinylestradiol is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%